Effect of suryanamaskar on pain, workability and quality of life in college students with primary dysmenorrhea: an experimental study - Deepali Kishor Deo; Priti Lendghar (International Journal Of Community Medicine And Public Health, 2026)
Background: Dysmenorrhea is a common gynecological issue affecting women of all ages, especially adolescents and young adults, affecting 67% to 90% of women aged 17-24 years. Pain in dysmenorrhea can severely impact daily life, leading to reduced concentration, absenteeism from college or work, and limited social engagement. These limitations directly affect quality of life, a concept defined by the World Health Organizations. Women with dysmenorrhea often experience lower quality of life scores, especially in areas such as physical functioning, bodily pain, general health, and vitality. Pharmacological treatments like NSAIDs and oral contraceptives are commonly used but may not be suitable for all. Yoga, particularly surya namaskar, has gained recognition as a safe and holistic approach. Methods: Sixty college going students participated in this study. Participants were selected based on the inclusion and exclusion criteria. Subjects were given suryanamaskar thrice a week for 8 weeks. Pre and post assessment was taken using three outcome measures that is numerical pain intensity scale (NPRS), work ability index score (WAI) and World Health Organization quality of life scale-Bref (WHOQOLBREF). Results: The present study included 60 female participants with a mean age of 22.15±2.02years. All changes were statistically significant (p=0.001), indicating that regular practice of surya namaskar had a substantial positive effect on pain reduction, work ability, and overall quality of life in females with primary dysmenorrhea. Conclusions: The study concluded that suryanamaskar is effective in reducing pain, enhancing workability and improving quality of life in college students with primary dysmenorrhea.